Anatomy, immunology, digestive physiology and microbiota of the salmonid intestine: Knowns and unknowns under the impact of an expanding industrialized production. Issue 107 (December 2020) - Bjørgen, Håvard; Li, Yanxian; Kortner, Trond M.; Krogdahl, Åshild; Koppang, Erling Olaf
Abstract: Increased industrialized production of salmonids challenges aspects concerning available feed resources and animal welfare. The immune system plays a key component in this respect. Novel feed ingredients may trigger unwarranted immune responses again affecting the well-being of the fish. Here we review our current knowledge concerning salmon intestinal anatomy, immunity, digestive physiology and microbiota in the context of industrialized feeding regimes. We point out knowledge gaps and indicate promising novel technologies to improve salmonid intestinal health. Highlights: Macro- and microscopic anatomy of the salmon gastrointestinal tract is reviewed. Digestive function and responses to variation in diet composition are presented. Known adverse reactions to feed are discussed. Present knowledge on gut microbiota in the fish intestine is summarized.